White spots in pharmaceutical pipelines–EMA identifies potential areas of unmet medical needs. Issue 3 (May 2015) - Papaluca, Marisa; Greco, Martina; Tognana, Enrico; Ehmann, Falk; Saint-Raymond, Agnès
<x xml:space="preserve">Abstract</x> Unmet medical needs are a priority for organizations such as the WHO and major public–private initiatives, such as Innovative Medicines Initiative, were established to speed up the development of better and safer medicines for patients. To assist such projects, the EMA in its 'Road Map to 2015' considered the mapping of unmet medical needs as a priority. This study has identified medical conditions for which the EMA could not identify developments in the pharmaceutical pipelines, that is, 'white spots'. Our analysis was made using external data sources as well as mining data of the EMA. The main areas for white spots were oncology, infectious diseases and certain psychiatric conditions. According to our data and a review of literature, in a number of these white spots, diagnostic tools may even be missing. The identification of those conditions will benefit stakeholders, including regulators, research funding bodies and patients' organizations.